2021
DOI: 10.3390/mi12121521
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art of Non-Invasive Electrode Materials for Brain–Computer Interface

Abstract: The brain–computer interface (BCI) has emerged in recent years and has attracted great attention. As an indispensable part of the BCI signal acquisition system, brain electrodes have a great influence on the quality of the signal, which determines the final effect. Due to the special usage scenario of brain electrodes, some specific properties are required for them. In this study, we review the development of three major types of EEG electrodes from the perspective of material selection and structural design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 116 publications
0
13
0
Order By: Relevance
“…The use of dry of Ag/AgCl and Ag-plated Cu electrodes for signal acquisition improves the convenience of use and effectively prevents the problem of conductive gels hardening. However, the dry electrodes may undergo oxidation, causing higher contact impedance [54] and affecting EEG signal acquisition. Moreover, this technique is suitable for functional brain activity observation [55] but cannot be used to assess cerebral blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dry of Ag/AgCl and Ag-plated Cu electrodes for signal acquisition improves the convenience of use and effectively prevents the problem of conductive gels hardening. However, the dry electrodes may undergo oxidation, causing higher contact impedance [54] and affecting EEG signal acquisition. Moreover, this technique is suitable for functional brain activity observation [55] but cannot be used to assess cerebral blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other conducting materials, such as gold and microporous titanium, [94][95][96] conducting polymer poly(3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT:PSS), [97][98][99] carbon nanotubes (CNTs), 100 and graphene, [101][102][103] have also been investigated for their possible use in EEG electrodes. For example, Leleux et al fabricated a flexible EEG electrode via depositing PEDOT:PSS on a polyimide substrate and obtain a signal-to-noise ratio (SNR) of 24.4 dB when measuring the somatosensory evoked potentials (Fig.…”
Section: Categories Of Eeg Electrodesmentioning
confidence: 99%
“…19–21 In these studies, the role of the electrode has been found to be essential in neural interface technology, where its performance can directly affect the quality of signal acquisition and the efficiency of signal processing. 22…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In these studies, the role of the electrode has been found to be essential in neural interface technology, where its performance can directly affect the quality of signal acquisition and the efficiency of signal processing. 22 Throughout the history of neural interfaces, material and structural innovations are two key factors that drive the advances in neural interfaces (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%